N-Benzoimidazole/Oxadiazole Hybrid Universal Electron Acceptors for Highly Efficient Exciplex-Type Thermally Activated Delayed Fluorescence OLEDs - Wenbo Yuan; Hannan Yang; Mucan Zhang; Die Hu; Ning Sun; Youtian Tao (Frontiers in Chemistry, 2019)
Recently, donor/acceptor type exciplex have attracted considerable interests due to the low driving voltages and small singlet-triplet bandgaps for efficient reverse intersystem crossing to achieve 100% excitons for high efficiency thermally activated delayed fluorescence (TADF) OLEDs. Herein, two N-linked benzoimidazole/oxadiazole hybrid electron acceptors were designed and synthesized through simple catalyst-free C-N coupling reaction. 24iPBIOXD and iTPBIOXD exhibited deep-blue emission with peak at 421 and 459 nm in solution, 397 and 419 nm at film state, respectively. The HOMO/LUMO energy levels were −6.14/−2.80 for 24iPBIOXD and −6.17/−2.95 eV for iTPBIOXD. Both compounds could form exciplex with conventional electron donors such as TAPC, TCTA, and mCP. It is found that the electroluminescent performance for exciplex-type OLEDs as well as the delayed lifetime was dependent with the driving force of both HOMO and LUMO energy offsets on exciplex formation. The delayed lifetime from 579 to 2,045 ns was achieved at driving forces close to or larger than 1 eV. Two TAPC based devices possessing large HOMO/LUMO offsets of 1.09–1.34 eV exhibited the best EL performance, with maximum external quantum efficiency (EQE) of 9.3% for 24iPBIOXD and 7.0% for iTPBIOXD acceptor. The TCTA containing exciplex demonstrated moderate energy offsets (0.88–1.03 eV) and EL efficiency (~4%), while mCP systems showed the poorest EL performance (EQE <1%) and shortest delayed lifetime of <100 ns due to inadequate driving force of 0.47–0.75 eV for efficient exciplex formation.